Relationship of job security, job stress and organization support with job satisfaction among teachers in Seri Manjung Sub District, Perak - Nur Syazwani, Suhaimi (2016)
This study examines the relationship of job security, job stress and organization support towards job satisfaction of teachers in Seri Manjung, Perak. In addition, this study tries to determine which of the three variables namely job security, job stress and organization support lead more to job satisfaction. Correlation study and proportionate stratified sampling were used in the study. The data were collected from 189 respondents by using a structured questionnaire and then were analyzed using SPSS Version 22.0 software. Results of the study indicate that there is a significant positive relationship between job security and job satisfaction. Results of study also indicate that there is a significant negative relationship between job stress and job satisfaction. Besides that, there is a significant positive relationship between organization support and job satisfaction. Lastly, there is a simultaneous significant influence of job security, job stress and organization support towards job satisfaction. Organization support shows the greater impact on job satisfaction of teachers in Seri Manjung, Perak compare to other variables. The implication of these findings for theoretical and practical aspect is discussed accordingly.